The effect of new cultural phenomenon’s оn a transformation of a psychoculture of the personality - Ардашова, Я. І. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
Disclosed the features of the emergence and formation of new cultural phenomena. It was shown of the effect of cultural phenomenon’s оn a transformation of a psychoculture of the personality in the information age.